Neonatal hypoxic‐ischaemic encephalopathy: what lies ahead?. (20th June 2014) - Colditz, Paul
<x xml:space="preserve">Abstract</x> This commentary is on the original article by Natarajan et al. on pages 1052–1058 of this issue.